Ancient Hebrew inscriptions : corpus and concordance - Davies, Graham I.; Bockmuehl, Markus N. A.; De Lacey, D. R. (De Lacey, Douglas R.); Poulter, A. J. (Poulter, Andrew J.) (Cambridge University Press, 2004)
This is the sequel to the first volume of Ancient Hebrew Inscriptions: Corpus and Concordance, published in 1991. It contains some 750 inscriptions from the Old Testament period which were mainly published for the first time between 1990 and 2000. Some were discovered in regular archaeological excavations, others come from private collections. The new material includes ostraca from different sites, which are of religious, literary and historical importance, and extensive information about the personal names which were in use in the biblical period. The number of coin-legends and other texts from the Persian and early Hellenistic periods has also been enlarged. Each text is supplied with a brief description, an approximate date and publication information. The concordance provides an easy way to discover which Hebrew words and proper names occur in non-biblical sources and helps greatly to widen the basis for Hebrew language study.